Analisis Penerapan Sistem Pengendalian Internal atas Pengelolaan Barang Milik Negara pada Kantor Wilayah Kementerian Hukum dan HAM Provinsi Bangka Belitung - Novika Novika (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2021)
This study aimed to analyze the implementation of Internal Control System (SPI) for the Management of State Property in the Regional Office of The Ministry of Law and Human Rights (Kemenkumham) of Bangka Belitung Province. This study uses qualitative method with descriptive type. The data used was primary data, using interview technic and documentation. The results obtained are the Control Environment, Risk Assessment, Control Activities, Information and Communication, and Monitoring which are component of Internal Control System (SPI) have been implemented properly.